STRATEGI PENGELOLAAN KEUANGAN KELUARGA DIMASA PANDEMI COVID-19 (KELUARGA PENERIMA BANTUAN SOSIAL TUNAI DI KELURAHAN TURIDA) - Rismawati Rismawati; Hery Astika Putra (Nusantara Hasana Journal, 2021)
This research is entitled "Family Financial Management Strategy in the Covid-19 Period. (Family Recipient of Social Cash Assistance in Turida Family)”. The purpose of this study was to determine the financial management strategies of the families of cash social assistance recipients and to find out what are the obstacles in the financial management of the families of cash social assistance recipients in the Turida village which is the research location. This type of research is qualitative research with hermeneutic phenomena approach and data collection techniques, namely interviews, observation and documentation. The results of this study indicate that the families or households receiving cash social assistance have not fully managed family finances properly, because 3 out of 10 informants were able to separate their expenses based on a priority scale, while 7 other informants did not record or manage their finances, they only spent money. according to the needs and desires without priority, this can be seen from several obstacles experienced by the beneficiary housewives, such as the level of education, income, length of household and number of family members so that family financial management strategies can be carried out by beneficiary housewives. social cash, among others 1) Determine the priority scale in meeting needs, 2) Make a financial plan to differentiate between needs and wants, 3) make an ideal expenditure budget, 4) Make savings wisely when shopping and check daily expenditure budgets by making daily and monthly spending records , 5) Be wise in taking debt, 6) Doing something that can increase income, such as opening a small business.